ANALISIS PENGARUH PENDAPATAN ASLI DAERAH PROVINSI SUMATERA UTARA DALAM MENYEJAHTERAKAN RAKYAT SUMATERA UTARA DALAM PERSPEKTIF EKONOMI ISLAM - Nasution, Salman; Amsari, Syahrul; Munasip, Adi (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2023)
The welfare of a region can be seen from how the North Sumatra government utilizes a directed and accountable APBD. PAD has a major effect on welfare such as education, health and community income. North Sumatra's PAD has fluctuated but tends to decline, meaning that PAD has not been able to respond to human rights. there are still many unemployed and poor, high crime rates, low quality education is a variable of the welfare of the people of North Sumatra is still low. The type of research is descriptive research using explanatory. The results of the study concluded that North Sumatra's local revenue in the 5 (five) years from 2017 to 2021 experienced fluctuations but tended to be deficit towards welfare programs. In Islam, welfare issues must be addressed because there are human rights. the magnitude of Allah's creation in the sky and on earth, let alone the magnitude of North Sumatra's natural potential, certainly leads to welfare. However, PAD has not yet reached the welfare of the community. There is a need for policy reform and structural reform that can improve welfare.